Optimization of various factors affecting Agrobacterium-mediated transformation and regeneration of putative transgenic Malaysian MR219 rice with Bacillus SP 289 endo-β-1,3-1,4-glucanase gene - Rahman, Zuraida Ab; Amin, Noriha Mat; Rahim, Mohd Yusof Nor; ErnyYunus, Azlinda; Redzuan, Rohaiza Ahmad; Rashid, Muhamad Ridzuan; Ramli, Asfaliza; Othman, Ayu Nazreena; Hashim, Marzukhi; Kamaruzaman, Rahiniza; Subramaniam, S. (Emirates Journal of Food and Agriculture, 2017)
Sheath blight disease caused by Rhizoctonia solani is the most destructive diseases in rice cultivation. Development of transgenic indica rice MR219 through Agrobacterium tumefaciens strain EHA 105 harbouring the plasmid pCAMBIA 1305.2 with endo-beta-1,3-1,4-glucanase gene from Bacillus SP 289 is one of the strategies to engineer disease resistance. Four optimisation parameters were examined such as Agrobacterium culture cell density (0.1 to 1.0 based on OD600nm), callus immersion time in the Agrobacterium culture (30 to 120 minutes), duration of the subsequent drying time (15 to 120 minutes) and co-cultivation period (1 to 6 days). Hygromycin-resistant embryogenic calli developed after 8 to 10 weeks of transformation. Improved transformation rates were achieved when calli were incubated with an Agrobacterium suspension with a culture density of OD 600nm 0.2 for 30 mins, followed by 90 mins of drying time and co-cultivation for 3 days. PCR analysis of the transformants confirmed the presence of Bacillus SP 289 endo-beta-1,3-1,4-glucanase and hpt genes in the rice genome. The transgenic rice plants obtained in this study will be tested against sheath blight disease.